The drowning summer - Herman, Christine Lynn (Little, Brown and Company, 2022)
Sixteen-year-old fledgling mediums Mina and Evelyn navigate their growing attraction as they investigate the connection between a vengeful spirit and murders that rocked their costal Long Island town six years ago.